Nursing of a case of upper extremity edema treated with Sanse prescription (三色方治疗肢端水肿1例护理体会) - ZHANG Sijia (张思佳); MENG Jia (孟佳) (Association of Integrative Nursing, 2023)
This article summarized the observation on the effect of using the self prepared Sanse formula to treat patients with upper extremity edema. The mechanism and consequence of upper extremity edema, prescription composition of Sanse formula and procedure of external application were summarized. On the basis of routine nursing, the application of Sanse formula to the local affected part can improve the symptoms of patients with upper extremity edema, without adverse reactions, and has a positive meaning for promoting the rehabilitation of patients. (本文总结1例ICU患者肢端水肿的护理体会, 包括肢端水肿的发生机制以及不良影响、中药三色方的药方组成和外敷方法等。在常规护理的基础上应用三色方外敷, 能有效缓解患者上肢水肿症状, 对促进患者康复具有积极意义。)